Peningkatan Kemampuan Pemecahan Masalah Fisika Siswa Menggunakan Metode Praktikum Di Kelas X MAN Sipirok - Elisa Elisa; Ainun Mardiyah; Aslamiyah Rambe (Universitas Muhammadiyah Tapanuli Selatan, 2019)
his study aims to improve the ability to solve physics problems and student learning outcomes in the materials of Straight Motion Kinematics with the initial ability to use ordinary practicum methods and practicum methods with different procedures. This research is a Classroom Action Research (CAR) with two cycles. The subject of this research is class X MIA 2 MAN Sipirok, each class totaling 30 students. Class X MIA 2 uses practicum procedures commonly used in schools. The treatment instruments used were syllabus and lesson plans, and for the test instrument used five questions for problem-solving skills and ten questions for student learning outcomes. The results obtained are the ability to solve physics problems in class XI MIA 2. After learning with practicum methods, the ability to solve problems and student learning outcomes increase. This is indicated by (1) Learning outcomes using the demonstration method have increased from cycle I students who did not pass 70% and passed 30%, in cycle II students who did not pass 25% and passed 75%. This happens because the demonstration method used in the first cycle is the usual demonstration method and in the second cycle uses a demonstration method with different procedures. (2) Aspect of problem-solving according to the indicator of problem-solving has increased namely identifying aspects in the first cycle of 43.52% and the second cycle to 72.53%, aspects of implementing the strategy in the first cycle 56.42% and in the second cycle to 77.63 %, aspects of formulating Physics problems in the first cycle 33.90% and in the second cycle to 76.72%, aspects of interpreting Physics problems in the first cycle 53.52% and in the second cycle to 86.15%. Keywords: Problem-solving ability, Classroom Action Research, MAN Sipirok